2018
DOI: 10.1096/fj.201801846r
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulated expression of microRNA‐338‐5p contributes to neuropathology in Alzheimer's disease

Abstract: Alzheimer's disease (AD) is a leading cause of dementia. However, the mechanisms responsible for development of AD, especially for the sporadic variant, are still not clear. In our previous study, we discovered that a small noncoding RNA (miR‐188‐3p) targeting β‐site amyloid precursor protein cleaving enzyme (BACE)‐l, a key enzyme responsible for Aβ formation, plays an important role in the development of neuropathology in AD. In the present study, we identified that miR‐338‐5p, a new miRNA that also targets B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…Downregulated miR-29a/29b1/c, miR-338-5p and miR-16 are all linked to increased Aβ-mediated neurotoxicity in vitro and in vivo [113]. Among those microRNAs, miR-338-5p also regulates NF-kB signaling and promotes neuroinflammation [122]. In vivo studies with mouse models also showed that miR-34a promotes Aβ accumulation and cognition by promoting BACE-1 expression and β-secretase activity.…”
Section: Ncrnas In the Regulation Of Aβ Generation And Accumulationmentioning
confidence: 98%
See 1 more Smart Citation
“…Downregulated miR-29a/29b1/c, miR-338-5p and miR-16 are all linked to increased Aβ-mediated neurotoxicity in vitro and in vivo [113]. Among those microRNAs, miR-338-5p also regulates NF-kB signaling and promotes neuroinflammation [122]. In vivo studies with mouse models also showed that miR-34a promotes Aβ accumulation and cognition by promoting BACE-1 expression and β-secretase activity.…”
Section: Ncrnas In the Regulation Of Aβ Generation And Accumulationmentioning
confidence: 98%
“…miR-16 can reduce BACE1 expression and attenuate Aβ-mediated neurotoxicity. miR-338-5p also regulates BACE-1 expression by targeting its mRNA, and expression of this micro-RNA leads to increased Aβ formation in brain tissues [122]. Downregulated miR-29a/29b1/c, miR-338-5p and miR-16 are all linked to increased Aβ-mediated neurotoxicity in vitro and in vivo [113].…”
Section: Ncrnas In the Regulation Of Aβ Generation And Accumulationmentioning
confidence: 99%
“…This is an important finding that would corroborate the theory of vascular dysfunction and hypoperfusion during the pathogenesis of AD ( Govindpani et al, 2019 ). Similarly, overexpressed miRNA-338 targets BACE1 and reverts neuroinflammation and Aβ-amyloid formation ( Qian et al, 2019 ). Interestingly, the knockdown of this miRNA by the injection of the miRNA-338-sponge in mice brain promoted spontaneous neoplasm formation, histologically reminiscent of GBM with neuronal morphological disorganization and increased proliferation ( Howe et al, 2017 ).…”
Section: Mirnas As Modulators Of Parkinson’s and Alzheimer’s Diseasesmentioning
confidence: 99%
“…In learning memory aspects, miR-124 and miR-181a, which are two miRNAs that are upregulated in the hippocampus, are directly associated with deficits in synaptic plasticity [ 83 , 84 ]. Similarly, overexpression of miR-338-5p and miR-181 functionally prevented impairments in synaptic plasticity, learning ability, and memory retention in an animal model of AD [ 85 , 86 ]. Furthermore, overexpression of miR-153 has provided new insight into the molecular mechanism of presynaptic plasticity impairment at the miRNA level and suggests that chronic brain hypoperfusion obstructs presynaptic vesicle fusion with the presynaptic membrane via miR-153-mediated downregulation of multiple synaptic vesicle-related proteins [ 87 ].…”
Section: Main Textmentioning
confidence: 99%